GENDER DIFFERENCES AT THE WORKPLACE: SICKNESS ABSENCE AND PRODUCTIVITY LOSS AT WORK AND THEIR ASSOCIATION WITH HEALTH AND WORK-RELATED FACTORS - Djikanović, Bosiljka; Kouwenhoven-Pasmooij, Tessa A.; Kraaijenhagen, Roderik A.; Roeters van Lennep, Jeanine E.; Burdorf, Alex; Vasilev, Vladimir; Robroek, Suzan J.W. (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Differences in sickness absence and productivity loss at work between men and women are recognized but need to be better understood. Materials and methods: In a cross-sectional study, 10,407 employees from 37 companies in the Netherlands participated in a web-based health risk assessment, between 2010 and 2014. Self-reported short-term (
Keywords: gender differences; sickness absence; productivity loss at work; health; disease; psychosocial work-related factors